Electronic Journals and Magazines on the Internet - Denise Johnson (Networks: An Online Journal for Teacher Research, 1998)
Educators have always valued scholarly journals as a means of remaining current on research and informing instruction. In the last few years, the Internet has seen an increase in popularity and has brought about a new medium in scholarly publication. Educators are now able to access many of their favorite journals and magazines online!